2011
DOI: 10.1172/jci44641
|View full text |Cite
|
Sign up to set email alerts
|

Loss of H3K4 methylation destabilizes gene expression patterns and physiological functions in adult murine cardiomyocytes

Abstract: Histone H3 lysine 4 (H3K4me) methyltransferases and their cofactors are essential for embryonic development and the establishment of gene expression patterns in a cell-specific and heritable manner. However, the importance of such epigenetic marks in maintaining gene expression in adults and in initiating human disease is unclear. Here, we addressed this question using a mouse model in which we could inducibly ablate PAX interacting (with transcription-activation domain) protein 1 (PTIP), a key component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 40 publications
(56 reference statements)
4
93
0
1
Order By: Relevance
“…Furthermore, our experiments using isolated working hearts indicated that H3K9 was rapidly demethylated within 30 minutes in response to elevated cardiac preload, supporting the dynamic nature of H3K9 methylation as an epigenetic control mechanism of ANP and BNP in the heart. In contrast, H3K4 methylation was unchanged in failing hearts, in agreement with a recent study on adult cardiac myocytes in which reduction of overall H3K4 levels by deletion of PAX interacting protein 1, a key component of the H3K4 complex, did not affect BNP expression and had only a small -and, paradoxically, activating -effect on ANP expression (36).…”
Section: Figuresupporting
confidence: 91%
“…Furthermore, our experiments using isolated working hearts indicated that H3K9 was rapidly demethylated within 30 minutes in response to elevated cardiac preload, supporting the dynamic nature of H3K9 methylation as an epigenetic control mechanism of ANP and BNP in the heart. In contrast, H3K4 methylation was unchanged in failing hearts, in agreement with a recent study on adult cardiac myocytes in which reduction of overall H3K4 levels by deletion of PAX interacting protein 1, a key component of the H3K4 complex, did not affect BNP expression and had only a small -and, paradoxically, activating -effect on ANP expression (36).…”
Section: Figuresupporting
confidence: 91%
“…Recent studies in which KMT cofactors were disrupted in the mature heart and kidney have shown that H3K4me3 is important in specific aspects of adult terminally differentiated tissues, such as cardiac electrophysiology and renal concentrating mechanisms. 42,43 Given its strong association with actively transcribed genes, the broad distribution of H3K4me3 and its KMT, Ash2l, in nephron progenitors and derivatives is not surprising. Our studies in clonal MM-like cells have demonstrated that H3K4me3 peaks decorate not only actively transcribed metabolic and housekeeping genes, but also promoters of developmental renal regulators such as Six2 and Osr1.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing histone H3 lysine 4 methylation in differentiated cardiomyocytes results in deletion of PTIP protein. This increases the sensitivity of cardiomyocytes to premature ventricular complexes (124). In patients with advanced heart failure, epigenomic patterns have been observed (94), such as differential DNA methylation and trimethylation of lysine 36 of histone 3.…”
Section: Histone Modificationmentioning
confidence: 99%